Music Museum Designing Solutions According To Cultural Sustainability In Tabriz - Abr, Shahram Boluri; Alamdari, Lachin Pahlyan (The Turkish Online Journal of Design Art and Communication, 2016)
Tabriz is the capital and largest city of Azerbaijan, an ancient city that has a great reputation and also city of innovations in Iran. But it is worth to discuss about the weakness point of this great city with thousands of years of culture and civilization. While for such a large city which have great artists, have not been established a worthy museum of them. Building the first music museum in the North West and in the largest city of it means in the Tabriz, meanwhile led to development of the tourism industry in this city and also caused a cultural and artistic place to be for those interested in art and music. The aim of such a museum in Tabriz, can be giving attention to Azerbaijani culture and traditional music, create an appropriate architectural atmosphere to become familiar with a variety of musical instruments, designing and categorize the galleries based on a variety of instruments, creating an appropriate architectural atmosphere to gather the music artists and their related instruments, designing the cultural centers inside the Museum like specialized music library and amphitheater. In the literature review to gather the relevant information in this field will perform by library research and using reliable sources such as books, papers, and thesis. With designing questions, finding uncertainties in the research topic with an indication of the need for research and in the following with performing the library and scientific studies as well as field studies, this all will led us to find a suitable place for the project and finally answer the research questions.
Keywords: Museum; Music; Azerbaijan; Designing; Tabriz